Chemical and pharmacological characterization of aqueous and ethanolic extracts of Cyclamen hederifolium Ait. (Primulaceae) tuber - Kojičić, Ksenija; Arsenijević, Aleksandar; Marković, Marija; Stankov Jovanović, Vesna; Simić, Zoran; Tadić, Vanja; Cupara, Snežana (Vojnosanitetski pregled, 2021)
Background/Aim. Cyclamen hederifolium (C. hederifolium) Ait. belongs to the family Primulaceae, which includes 23 species of cyclamen, naturally distributed in the Central and Southern Europe, Western Asia and some parts of North Africa. This plant is considered highly poisonous and not suitable for human use. However, tuber extracts have been used in traditional medicine and homeopathy. The aim of this study was to investigate C. hederifolium growing naturally in Serbia for its metal content and biological activities (antioxidant, antibacterial, antifungal and cytotoxic activity). Methods. Content of metals was determined by atomic absorption spectrophotometric method. We used several different assays for assessment of antioxidant activity of both aqueous and ethanol extracts of C. hederifolium: 2.2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, 2,20-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging assay, ferric-reducing antioxidant power (FRAP) assay, total reducing power assay (TRP) and cupric reducing antioxidant capacity (CUPRAC) assay. The disk diffusion assay was used to investigate sensitivity of laboratory bacterial and fungal control strains against investigated extracts. Aqueous and ethanol extracts of C. hederifolium were examined on 4 different tumoral cell lines by in vitro MTT bioassay. Results. The presence of Mn, Ca, Mg, Fe, Zn, K, Cu was confirmed in aqueous and ethanol extract, as well as in whole tubers and soil, while Cr, Ni, Pb and Cd were not detected. Both aqueous and ethanol extract of C. hederifolium tubers showed antioxidant activity, that positively correlated to content of phenols and flavonoids in it. Aqueous extract was slightly superior in these terms than ethanol one. None of the tested extracts showed antimicrobial activity. Both investigated extracts showed cytotoxicity against four cancer cell lines 4T1, HCT116, CT26, LLC1, in the concentration range 15,625–2,000 μg/mL. Ethanol extract showed stronger cytotoxicity than aqueous extract. Conclusion. Seven metals were identified in the C. hederifolium tubers, extracts and soil. Both extracts exhibited antioxidant and cytotoxic activity.